2015
DOI: 10.3390/s150305228
|View full text |Cite
|
Sign up to set email alerts
|

Human Computer Interactions in Next-Generation of Aircraft Smart Navigation Management Systems: Task Analysis and Architecture under an Agent-Oriented Methodological Approach

Abstract: The limited efficiency of current air traffic systems will require a next-generation of Smart Air Traffic System (SATS) that relies on current technological advances. This challenge means a transition toward a new navigation and air-traffic procedures paradigm, where pilots and air traffic controllers perform and coordinate their activities according to new roles and technological supports. The design of new Human-Computer Interactions (HCI) for performing these activities is a key element of SATS. However eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Expert systems that contain intelligent agents have been applied to improve the reliability and maintainability of avionics systems [3]. A new generation of airborne human-computer interaction systems has been developed based on multi-agent systems to enhance situation awareness and decision-making through the pilot cockpit [4]. Furthermore, recent studies have revealed that the SOA can help an avionics system not only improve its flexibility but also reduce the cost and human-computer interaction of updating features [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Expert systems that contain intelligent agents have been applied to improve the reliability and maintainability of avionics systems [3]. A new generation of airborne human-computer interaction systems has been developed based on multi-agent systems to enhance situation awareness and decision-making through the pilot cockpit [4]. Furthermore, recent studies have revealed that the SOA can help an avionics system not only improve its flexibility but also reduce the cost and human-computer interaction of updating features [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Special Issue gathers together 22 papers concerning current research efforts focused on human-computer interaction (HCI) through natural and intuitive modalities including hand/body gestures [ 1 , 2 , 3 , 4 , 5 , 6 ], face recognition [ 7 , 8 ], gaze/eye tracking [ 4 , 9 , 10 ], biosignal analysis [ 11 , 12 , 13 , 14 , 15 ], speech recognition [ 16 ], activity recognition [ 17 , 18 ] and their related issues. Moreover, the Special Issue contains papers related to the architectural design of smart environments [ 19 , 20 ], with a particular focus on the exploitation of sensors for gathering information related to the environment [ 21 , 22 ]. In the following, an overview of the papers included in the Special Issue is provided, by summarizing their main contribution to the state-of-the-art.…”
mentioning
confidence: 99%
“…Human-computer interaction in aircraft navigation systems plays a key role for enhancing situation awareness and supporting decision-making processes. In this sense, the work proposed by Canino-Rodríguez et al [ 20 ] represents a step towards the development of smart air traffic systems where inputs coming from sensors provide the pilot with controller indications as well as surrounding traffic situation through the cockpit. In particular, this work proposes a distributed functional architecture based on a multi-agent approach, with the final aim of sketching a list of guidelines useful in the design of cockpit human-computer interaction.…”
mentioning
confidence: 99%